Current Approaches to Desensitization in Solid Organ Transplantation - Schinstock, Carrie; Tambur, Anat; Stegall, Mark (Frontiers in Immunology, 2021)
Major advancements in the development of HLA antibody detection techniques and our understanding of the outcomes of solid organ transplant in the context have HLA antibody have occurred since the relevance of sensitization was first recognized nearly 50 years ago. Additionally, kidney paired donation programs (KPD) have become widespread, deceased donor allocation policies have changed, and several new therapeutic options have become available with promise to reduce HLA antibody. In this overview we aim to provide thoughtful guidance about when desensitization in kidney transplantation should be considered taking into account the outcomes of HLA incompatible transplantation. Novel therapeutics, desensitization endpoints, and strategies for future study will also be discussed. While most of our understanding about desensitization comes from studying kidney transplant candidates and recipients, many of the concepts discussed can be easily applied to desensitization in all of solid organ transplantation.